NONSTOICHIOMETRY AND THE LONG-RANGE CATION ORDERING IN CRYSTALS OF (NA1/2BI1/2)TIO3 - PARK, SE; CHUNG, SJ; KIM, IT; HONG, KS (AMER CERAMIC SOC, 1994)
Crystals of (Na1/2Bi1/2)TiO3 have grown by the flux technique and the Czochralski method. Nonstoichiometry, twin configurations, and long-range cation ordering in the crystals have been investigated using X-ray diffraction and an optical polarizing microscope. It has been found that nonstoichiometry was induced in the crystal grown by the Czochralski method owing to the volatilization of Bi-rich phase during the crystal growth. This nonstoichiometry in the crystal resulted in less lattice distortion from cubic symmetry, a lower degree of cation ordering, and a larger domain width in twin configuration. Variations in twinning with temperature and isotropization have been investigated.
Keywords: SODIUM-BISMUTH TITANATE; PHASE-TRANSITIONS; CERAMICS